Isolation, Purification and Quantification of Quercetin and Primary Metabolites from Onion (Allium cepa L.): Isolation, Purification, Quantification of Quercetin from Onion - Ahmed, Asma; Gulfraz, Muhammad; Khalique, Noman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Plants constitute a key component of drug in fold system, and thus are a source of inspiration for many drugs. This study was conducted to quantify carbohydrates, proteins, lipids, metal ions and flavonoids in the bulbs of three different varieties of Allium cepa L. Gas chromatography (GC) analysis was performed for analysing fatty acids while high-performance liquid chromatography (HPLC) was employed for quantification of Quercetin. Results of this investigation revealed that dark pink A. cepa contains higher concentration of cellulose (17.55%) and lower concentration of oil (2.12 %) and its GC analysis showed that propionate concentration was much higher (31.61 %). Levels of protein and crude fat in the onion samples were 8.75% and 9.9%, respectively. Macro elements were observed in high concentration and sodium was highest (14.0 μg/mL); however, copper concentration was observed to be in traces (0.3 μg/ mL). The HPLC analysis of flavonoids revealed that A. cepa was rich in Quercetin-3, 4- O-diglucoside (3, 4- Qdg); Quercetin-3-O-glucoside (3-Qmg or iso quercitrin); Quercetin-4 -O-glucoside (4-Qmg); Isorhamnetin-3-O-glucoside (3-Img), Quercetin aglycone (Q); and Kaempferol (K) in which concentration of Quercetin-4 - O-glucoside (4 - Qmg) was significantly higher. The present study helped in purification of fatty acids and quercetin and for formulation of drugs which utilize these phytochemicals.